OPTIMALISASI DAYA SISTEM HIBRID PHOTOVOLTAIC DENGAN SUATU SISTEM PHOTOVOLTAIC THERMAL SEBAGAI SUMBER ENERGI LISTRIK DAN SISTEM PEMANAS AIR - Musfirah Putri Lukman; Junaedy (STMIK KHARISMA Makassar, 2015)
One method to optimize the output power of photovoltaic modules is to build a Hybrid photovoltaic system in this case the manufacture of water heating systems by utilizing solar energy through a photovoltaic system. This system uses a photovoltaic module and an extraction box containing 17 spiral-shaped copper pipes. This system is controlled by the ATMega 8535 microcontroller to activate the Windshield Whiser Pumper at 450C to pump fluid into the pipe. System testing was carried out for 3 different types of material namely water, thermal oil and air. The test was carried out on 3 different weather conditions for water material namely sunny, cloudy and cloudy weather conditions and data collection was carried out for 5 hours at certain hours. The test results show the best value of total power efficiency obtained by water material in sunny weather conditions of 67.99%, followed by thermal oil media of 21.06% and finally air material. Hot water produced from pipes can be used for bathing and sterilizing medical devices